The Kingdom of Saudi Arabia and the United States of America. (c2018) - Hammoud, Zeinab (2018)
The relationship between Saudi Arabia and the United States is crucial to understanding the current state of play in the Middle East. Yet the dynamics of the relationship itself are far more difficult and contested. While liberal international relations theorists see the relationship as fraught largely economic, a realist theory demonstrates that the perseverance of the relationship rests on mutual interests rooted in the desire to maintain the status quo. By analyzing the historical development of the Saudi-US relationship, this thesis shows how the realist perspective can be used to provide an insightful analysis into the history of relations between Saudi Arabia and the US. Using a comparative historical perspective, the thesis unravels that interests and ideology are not necessarily complementary. Since 9/11, there have been significant ideological divergences in perceived interests on both sides, yet long term economic and security interests prevailed. The significance behind this finding lies in the fact that while President Donald Trump is in the White House while Crown Prince Muhammad Bin Salman in control of Saudi foreign policy, the relationship between both countries has been consolidated in a realist framework. Thus, understanding the dynamics from a realist perspective that have underpinned the relationship in recent years is crucial to the framing of both countries foreign policy outlooks.